12x-13=-6x

Simple and best practice solution for 12x-13=-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-13=-6x equation:


Simplifying
12x + -13 = -6x

Reorder the terms:
-13 + 12x = -6x

Solving
-13 + 12x = -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-13 + 12x + 6x = -6x + 6x

Combine like terms: 12x + 6x = 18x
-13 + 18x = -6x + 6x

Combine like terms: -6x + 6x = 0
-13 + 18x = 0

Add '13' to each side of the equation.
-13 + 13 + 18x = 0 + 13

Combine like terms: -13 + 13 = 0
0 + 18x = 0 + 13
18x = 0 + 13

Combine like terms: 0 + 13 = 13
18x = 13

Divide each side by '18'.
x = 0.7222222222

Simplifying
x = 0.7222222222

See similar equations:

| 6a-9-8a+5a= | | 5x+200=3x-300 | | -23n+13n+47-5n=-28 | | 3l+4-4l=-3 | | 53+18w=c | | 7x-4=37 | | 3(t-3)-2t=-30 | | (2m+3t)(3m-4t)= | | y=6000(1+0.04)5 | | 9x-8=8x+1 | | x^3-13x^2-2x+26=0 | | 7-3x-(-5x+2)+1+7x=5x | | 2x+4x-9x+7= | | 5(20x+25)=925 | | 10*xy+90=72x | | 12y-5y-7+4= | | 10x-50=7x+1 | | x-(5-2x)=1+(2+x) | | 2+(-3)(4)-(-5)= | | 15=-7+44y | | -100=x^2-29x | | 10x=1+5x | | 14+12y=16+9y | | .25x+9=1 | | 28-7x=-28x-28 | | X-13.6=-16 | | 12x-42+3x=6(3x-9) | | -23+13n+47-5n=-28 | | 5.3+(w+1.2)= | | -2u+1.4=-0.6 | | 10x=5+1x | | -2(b+7)=3b+7-5b |

Equations solver categories